Ethno-veterinary Potential of Underutilised Millets from Bahraich: An overview - Mall, Tej Pratap (Jour Med Resh and Health Sci, 2019)
Millet is one of the oldest foods known to humans and possibly the first cereal grain for domestic purposes. Millet is tasty, with a mildly sweet, nut-like flavour and contains a myriad of beneficial nutrients